Penerapan Ice Breaking Sebagai Efektivitas Belajar Mengajar pada Siswa Kelas II di SD Negeri 02 Bintaro - Mawar Dwi Aprillia Firdaus; Hindun Hindun (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research aims to describe the application of ice breaking as the effectiveness of teaching and learning in elementary schools. This research was carried out at SDN 02 Bintaro in November 2023. The research approach used was qualitative using interview and observation techniques. The data source was taken from the author's interview with a class II B teacher. This research involved a class II B teacher at SDN 02 Bintaro and students in that class. Data collected from interviews and observations shows that the class II B teacher has implemented ice breaking before learning begins and in the middle of learning with the aim of raising students' enthusiasm and re-optimizing the learning situation which was initially not conducive. The results of the effectiveness of implementing ice breaking in the classroom are that it can increase students' enthusiasm for learning, foster students' interest in learning, and increase concentration in the learning process. Keywords: ,,,